Geomorphological analysis and fluvial dynamics of the Huallaga River in Yurimaguas distric - Ramos Alonzo, Robert B. (2020)
The Huallaga River is one of the main Amazon rivers. The research area located in the Amazon plain is characterized by presenting a homogeneous relief, however due to the dynamics of the river the physiographic aspect is varied, these range from the flood areas to higher areas called hills. The flow regime varies throughout the year, showing months of low water and others with abundant recharge, the average flow is 2 969.5 m3/s, in the research area the average width is 325 m and has a maximum depth of 16 m. Due to its dimensions, the Huallaga river presents a great dynamism, evidencing that in the period of analysis it has occurred in a sector, which has changed its direction, leaving an abandoned channel, the dynamics is along its bed, noting that in the areas where the river changes direction, it has migrated even up to more than 2 km.